2006
DOI: 10.1002/jcb.20864
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow induces Rankl expression in primary murine calvarial osteoblasts

Abstract: Mechanical loading of bone generates fluid flow within the mineralized matrix that exerts fluid shear stress (FSS) on cells. We examined effects of FSS on receptor activator of nuclear factor kappa B ligand (RANKL), a critical factor for osteoclast formation. Primary murine osteoblasts were subjected to pulsatile FSS (5 Hz, 10 dynes/cm(2)) for 1 h and then returned to static culture for varying times (post-FSS). Protein levels were measured by Western analysis and mRNA by Northern analysis, RT-PCR and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…Mechanical stimuli include tensile force (8,9,(11)(12)(13)(14), compressive force (7,10,(15)(16)(17), hydrostatic pressure (18), sheer stress (19,20), rotative stress (21) and others (22,23). Stimulation with tensile force using a Flexercell tension system suppresses osteoclast differentiation and fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical stimuli include tensile force (8,9,(11)(12)(13)(14), compressive force (7,10,(15)(16)(17), hydrostatic pressure (18), sheer stress (19,20), rotative stress (21) and others (22,23). Stimulation with tensile force using a Flexercell tension system suppresses osteoclast differentiation and fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Such local mechanical stimuli result in mechanotransduction, the conversion of a physical signal into an intracellular biochemical cascade with the potential to alter gene expression, protein activity and ultimately cell function (Jacobs et al, 1998;Silver and Bradica, 2002;Pavalko et al, 2003;Batra et al, 2005;Iqbal and Zaidi, 2005;Epari et al, 2006;Isaksson et al, 2006;Leclerc et al, 2006;Liedert et al, 2006;Meikle, 2006). Loading induced dynamic fluid flow is a key regulatory factor in promoting healthy bone homeostasis (Frost, 1982;Weinbaum et al, 1994;Jacobs et al, 1998;McAllister et al, 2000;Bakker et al, 2001;Batra et al, 2005;Kim et al, 2006;Leclerc et al, 2006;Mehrotra et al, 2006;Tan et al, 2006;Tan et al, 2007). Given that oscillatory fluid flow promotes osteogenic activity in mature cells, it is our hypothesis that it is also a potent regulator of mesenchymal stem-cell differentiation down the osteogenic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies in vitro and in vivo have described the effects of mechanical stress on the bone cells. To investigate the influence of mechanical stress on the cells, several in vitro models have been established with varying methods, including sheer stress (fluid flow) (13,14) compressive (15,16) and tensile force (17), hydrostatic pressure (18), microgravity (19), and so on (20,21). Furthermore, in addition to an in vivo experimental system including transgenic mice, many studies have indicated the effect of mechanical stress on the bone's adaptive remodeling behavior in osteocytes (22), osteoblasts (23) and in a co-culture between osteoblasts and osteoclasts (24).…”
Section: Introductionmentioning
confidence: 99%